MXene Phase with C3 Structure Unit: A Family of 2D Electrides. (29th March 2021) - Bae, Soungmin; Espinosa‐García, William; Kang, Yoon‐Gu; Egawa, Noriyuki; Lee, Juho; Kuwahata, Kazuaki; Khazaei, Mohammad; Ohno, Kaoru; Kim, Yong‐Hoon; Han, Myung Joon; Hosono, Hideo; Dalpian, Gustavo M.; et al.
Abstract: A new structural phase is discovered for M2 CO2 MXenes with M = Sc, Y, La, Lu, Tm, and Ho. The hexagonal carbon layer sandwiched between M atoms, typical for MXenes, is transformed into C3 trimers with anionic electrons localized in quasi zero‐dimensional lattice spaces in‐between the C3 units, so the systems can be described as [M6 C3 O6 ] +II : 2e − electrides. The systems are readily ionized into [M6 C3 O6 ] +II with very low ionization energy via an anti‐doping mechanism. It is shown that this new structure of Sc2 CO2 can bind multiple lithium atoms, with low migration barriers. The findings indicate that these M2 CO2 MXenes with unusual carbon trimers are a new family of 2D electride insulators with the potential for charge storage applications, thermal field emission, and as anode material in lithium batteries. Abstract : The discovery of a family of 2D electride materials with composition M2 CO2 is reported, where M = Sc, Y, La, Lu, Tm, and Ho. The electride behavior emerges in a new structural phase for MXenes, where the hexagonal carbon layer is broken up into C3 trimers, and anionic electrons get trapped in the voids between the C3 units.